Answer:
Step-by-step explanation:
d
Answer:
Step-by-step explanation:
(x + 2)/2 = -2
x + 2 = -4
x = -6
(y + (-9))/2 = -1
y - 9 = -2
y = 7
(-6, 7)
answer is C
![\frac{AB}{BC}](https://tex.z-dn.net/?f=%20%5Cfrac%7BAB%7D%7BBC%7D%20)
=
![\frac{EB}{DC}](https://tex.z-dn.net/?f=%20%5Cfrac%7BEB%7D%7BDC%7D%20)
![\frac{AB}{BC}](https://tex.z-dn.net/?f=%20%5Cfrac%7BAB%7D%7BBC%7D%20)
=
![\frac{1.75 m}{7 m}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1.75%20m%7D%7B7%20m%7D%20)
let AB = E
⇒ (AB) (7 m) = (1.75 m) ( BC + AB)
(AB) (7 m) = (1.75 m) (1.5 m + AB)
= 2.625 m² + (1.75 m ) (AB)
(AB) (7 m - 1.75 m) = 2.625 m²
∴ AB = 2.625 m² ÷ (5.25 m)
<span>
⇒ the length of AB is 0.5 m</span>